Storyteller, Stenographer, and Self‑Published Superstar: How Astrid Lindgren’s Multiple Roles in Book Production Created the Lindgren Myth - Nauwerck, Malin (Mémoires du livre / Studies in Book Culture, 2022)
Astrid Lindgren holds a unique position within world literature, yet her enigmatic creative process has for many years been hidden in her impenetrable stenographed drafts and manuscripts. Because Lindgren through her employment at publishing house Rabén & Sjögren acted as her own editor and publisher, these drafts contain the entire creative and editorial – and to date inaccessible – process behind her literary works. With the purpose of unmasking Lindgren’s creative process as visible in her shorthand drafts and typed up manuscripts, this article applies the perspective of sociological editing (shaped particularly by McGann (1983) and McKenzie (1986) and more recently developed and applied for text genetic purposes by for example van Hulle (2008; 2014) and Gabler (2018)) to early results from The Astrid Lindgren Code. Focal points are 1) the secretarial skill of shorthand as the engine in Lindgren’s creative process, and its function in the interplay between the different production roles assumed by Lindgren 2) how the inaccessibility of her manuscripts, as well as the fact that Lindgren as author, editor, and publisher was her own ‘collaborator’ has contributed to reproducing an image of Lindgren as a solitary literary genius, or with Norwegian writer Alf Prøysen’s words, “a solar system of her own”.